Aplikasi Perancangan Informasi Kos Berbasis Android - Fanny Fatma Wati; Ratna Kurnia Sari; Tiara Dwi Aprilia (UNIVERSITAS RAHARJA, 2022)
seek knowledge and earn income by local people but also people from outside Tegal. This of course will make people from inside and outside Tegal look for temporary housing or boarding houses until their education or work is complete. The problem of finding boarding houses for students, employees, and the general public has become a classic problem that appears every year. Surely this is due to the unavailability of good information for boarding house seekers. Currently, the search for boarding houses for students, employees, or the general public still relies on information obtained from friends and other people. This is reversed during the current millennial revolution which is growing i. To find out the location of the desired boarding house, an application is needed which will later be made with the Basic4Android application. Basic4Android programming is a programming language which is one of the easiest to learn and develop until now. Basic4Android is a programming science developed in software and developed by the company Anywhere Software Ltd.